ВПЛИВ ПАНДЕМІЇ COVID-19 НА СТАН РИНКУ ПРАЦІ В УКРАЇНІ ТА СВІТІ - Todoruk, Sergy; Vodianka, Liubov; Todoriko, Iryna (My University, 2021)
Вплив, що зазнали провідні країни світу, спричинений пандемією Covid=19 у 2020 р. торкнувся усіх галузей економічного, соціального, культурного, туристичного, розважального життя кожного жителя планети. Такі події мають очевидні негативні наслідки в світовій економіці загалом та економіці певної країн. До них належать падіння ВВП, дисбаланс на ринку праці, зменшення чисельності працюючих, підвищення рівня бідності та ін. У березні 2020 р. рівень безробіття швидко зріс, і до квітня 2020 р. він значно перевищив свій попередній пік, що спостерігався під час Великої рецесії та одразу після неї. Найбільшого удару від впливу пандемії зазнали такі сектори економіки: транспорт, готельний та ресторанний бізнес, мануфактура та дрібна комерція. Зокрема, в Україні через пандемію коронавірусу з початку березня 2020 р. значно зросла кількість безробітних. Пік досяг 518 тис. осіб. Для адаптації в тих умовах, що склалися, світовий та вітчизняний ринок праці запровадили нові методи регулювання та функціонування. Світова економіка зазнала значних змін та перебудову її структури.
THE IMPACT OF THE COVID-19 PANDEMIC ON THE LABOR MARKET IN UKRAINE AND THE WORLD
The impact of all countries of the world caused by the Covid=19 pandemic in 2020 affected all areas of economic, social, cultural, tourist, entertainment life of every inhabitant of the planet. Such events have obvious negative consequences for the world economy as a whole and the economy of a particular country. These include falling GDP, labor market imbalances, declining employment, rising poverty, and more. In March 2020, the unemployment rate rose rapidly, and by April 2020 it had significantly exceeded its previous peak observed during and immediately after the Great Recession. The biggest impact of the pandemic was on sectors of the economy such as transport, hotels and restaurants, manufacturing and small business. In particular, in Ukraine due to the coronavirus pandemic since the beginning of March 2020, the number of unemployed has increased significantly. The peak reached 518 thousand people. Introduction of programs of the Government of Ukraine to ban the accrual of interest on overdue loans and liabilities; increase in the amount of assistance from the reserve fund to support unemployed citizens; promoting the development of small and medium=sized businesses, in particular the implementation of preferential credit programs "5=7=9", etc. On the other hand, more workload has been placed on businesses themselves. Thus, many companies at their own expense provided their employees with personal protective equipment and paid for their testing; disinfected the premises and, if necessary, ensured their delivery by transport to enterprises, etc. As a result of the analysis of the impact of Covid=19 on the world economy and Ukraine in particular, it should be noted that the world has undergone rapid transformational changes in all its areas. The crisis that arose in 2020 exceeded the scale of the crisis of the Great Depression. The world was forced to adapt to new living conditions for which it was not ready. This is reflected in indicators of unemployment and falling GDP. Ukraine, in turn, being in the recovery phase, after the difficult years of 2014—2018 in 2019 was able to partially stabilize the internal state of the economy and to some extent improve the situation in the labor market.To adapt to the current global and domestic labor market, new methods of regulation and operation have been introduced. The world economy has undergone significant changes and restructuring of its structure
Keywords: зайнятість; безробіття; ринок праці; карантин; пандемія; COVID 19; employment; unemployment; labor market; quarantine; pandemic